Characteristics of Asian American Family Caregivers of Older Adults Compared to Caregivers of Other Racial/Ethnic Groups: Behavioral Risk Factor Surveillance System 2015–2020. (May 2023) - Miyawaki, Christina E.; Bouldin, Erin D.; Taylor, Christopher A.; McGuire, Lisa C.; Markides, Kyriakos S.
Asian Americans (AAs) are the fastest-growing racial/ethnic minority group in the United States. While otherwise highly heterogeneous, AAs overall value filial piety and eldercare. This study compared the health and caregiving experiences of AA caregivers of older adults to AA non-caregivers and caregivers of older adults across racial/ethnic groups. We used 2015–2020 Behavioral Risk Factor Surveillance System data for 315 AA caregivers and 3822 AA non-caregivers, plus 395 American Indian/Alaska Native, 1883 Black, 1292 Hispanic, and 20, 321 non-Hispanic White caregivers. Among AAs, 4.3% were caregivers, a lower proportion than in other racial/ethnic groups. Most AA caregivers were female (59%), married (71%), in excellent/very good/good health (76%), and with at least one chronic health condition (66%). Other than relationship to care recipients, caregivers' experiences were similar across racial/ethnic groups: most cared for <20 hours/week and provided household and personal care. Efforts to support AA caregivers should be attentive to cultural practices.